PEMBELAJARAN BERBASIS OTAK (BRAIN BASED LEARNING), GAYA KOGNITIF KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR MAHASISWA - Widiana, I Wayan; Bayu, Gede Wira; Jayanta, I Nyoman Laba (Jurnal Pendidikan Indonesia, 2017)
This research purpose is to examine the effect of brain-based learning model on the ability to think creatively and student’s learning outcome. This type of research is experimental research design with non-equivalent control group design. Population of this research is the students of Semester V PGSD Ganesha University of Education which is consist of 8 classes. The samples were taken by random sampling technique as much as 2 classes. Data ability to think creatively and learning outcomes was collected by using test. Data collected were analyzed using ANOVA two lanes. Based on the results of data analysis, it’s found that the results of the study as follow. First, there are significant differences between the groups understanding of the concept of brain-based learning model and learning model Conventional group (F = 5.13; p <0.05). Second, there are significant differences between the groups understanding of the concept of cognitive style field independent and field dependent cognitive style groups (F = 23.43; p <0.05). Thirdly, in achieving an understanding of concepts, models of learning and cognitive style interacts significantly (F = 6.11; p <0.05). Fourth, there are significant differences between the groups ability to think creatively brain-based learning model and conventional learning model group (F = 12.75; p <0.05). Fifth, there are significant differences between the groups ability to think creatively cognitive style field independent and field dependent cognitive style groups (F = 44.94; p <0.05). Sixth, in the achievement of creative thinking ability, learning and cognitive style models do not interact significantly (F = 0.06; p> 0.05)